Preparation and Study of Some Mechanical Properties of Polymeric Films (PVA) Reinforced by CdCl2.H2O Salt - Akraam M. Sabbar; Sabah A. Salman; Rana S. Mahmood (Genius Journals, 2022)
In the present study, pure (PVA) polymer film and films reinforced with CdCl2.H2O salt with various values of the weight ratio ((3,7,11, and 15) wt%) were prepared with the use of the solution casting method. where mechanical properties, such as hardness and impact were studied For all composites films. Where the effects of weight ratio of salt on hardness (Shore D) of composite films was studied (PVA-CdCl2.H2O), The experimental results showed that the hardness increased with increasing the weight percentage of salt CdCl2.H2O. The additional value reaches its peak at the weight ratio (7wt %) and subsequently declines as the weight ratio of added salt rises. The impact of salt weight ratio on fracture energy and impact resistance of PVA-CdCl2.H2O composite films was investigated. It was discovered that raising the weight ratio of added CdCl2.H2O salt increases the value of fracture energy and impact resistance. In comparison to pure polymeric (PVA) film, the effect of weight ratio of salt on the tensile properties represented by ultimate tensile strength (U.T.S) and young's modulus (Ym) has been studied, and the values of the tensile properties represented by ultimate tensile strength (U.T.S) and young's modulus (Ym) of all composite films (at most weight ratios of the reinforcement with CdCl2.H2O).
Keywords: Polyvinyl Alcohol; CdCl2; Hardness; Fracture Energy